1996
DOI: 10.1101/gad.10.1.80
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal spermatogenesis in RXR beta mutant mice.

Abstract: We have generated mouse lines in which the RXRI3 gene was disrupted by homologous recombination. Approximately 50% of the RXR~ homozygous mutants died before or at birth, but those that survived appeared normal except that the males were sterile, owing to oligo-astheno-teratozoospermia. Failure of spermatid release occurred within the germinal epithelium, and the epididymis contained very few spermatozoa that, in addition, exhibited abnormal acrosomes and tails. There was a progressive accumulation of lipids w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
214
1
7

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 306 publications
(237 citation statements)
references
References 53 publications
15
214
1
7
Order By: Relevance
“…During the progression of VAD, this defect precedes the onset of testis degeneration. Of interest, a similar spermiation failure has been observed in rats under VAD conditions (Huang and Marshall, 1983;Huang et al, 1988), as well as in Rara-or Rxrb-null mutant mice (Lufkin et al, 1993;Kastner et al, 1996;Mascrez et al, 2004;Chung et al, 2005). Altogether, these data suggest that spermiation requires RA-liganded RAR␣/RXR␤ heterodimers in the seminiferous epithelium.…”
Section: Spermiation and Adhesion Of Germ Cells Are Highly Sensitive supporting
confidence: 66%
See 2 more Smart Citations
“…During the progression of VAD, this defect precedes the onset of testis degeneration. Of interest, a similar spermiation failure has been observed in rats under VAD conditions (Huang and Marshall, 1983;Huang et al, 1988), as well as in Rara-or Rxrb-null mutant mice (Lufkin et al, 1993;Kastner et al, 1996;Mascrez et al, 2004;Chung et al, 2005). Altogether, these data suggest that spermiation requires RA-liganded RAR␣/RXR␤ heterodimers in the seminiferous epithelium.…”
Section: Spermiation and Adhesion Of Germ Cells Are Highly Sensitive supporting
confidence: 66%
“…Second, the outcome of VAD in the seminiferous epithelium differs between these species: in VAD rats, spermatogenesis is arrested at the preleptotene spermatocyte stage (Huang and Humbree, 1979;Huang et al, 1990;Ismail et al, 1990), whereas in VAD mice, it is arrested at the spermatogonia stage (Huang and Hembree, 1979;Gaemers et al, 1997). Third, the functions of retinoid receptors in vivo are documented from the analysis of genetically altered mouse models (Lufkin et al, 1993;Kastner et al, 1996;Mascrez et al, 2004;Chung et al, 2005;Liu and Gudas, 2005) but not from rat models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the recent phenotypic characterization of all combinations of RXR (either a, b or g)/RAR (either a, b or g) compound mutants has provided genetic evidence supporting the proposal that RXR-RAR heterodimers act as functional units transducing the retinoid signal in vivo and furthermore has indicated that RXRa is the functionally predominant RXR in vivo (Kastner et al, , 1996a. In addition, it has been shown that RXRa null mutants are resistant to RA-induced limb defects (Sucov et al, 1995).…”
Section: Discussionmentioning
confidence: 84%
“…This is supported by the presence of retinoids in myogenic precursor cells (Wagner et al, 1990(Wagner et al, , 1992Chen et al, 1992) and RA-receptors in muscle tissue Dolle et al, 1994;GigueÁ re, 1994). However, the knock-outs of RARs and RXRs in the mouse to date did not compromise skeletal muscle development (Kastner et al, , 1996bSucov et al, 1994;Lohnes et al, 1995;Krezel et al, 1996) probably due to a large degree of functional redundancy among these receptors which prevented a de®nitive assignment of their physiological functions in the animal. To disable completely the retinoid pathway in skeletal muscle, it will be necessary to generate multiple knock-outs of RARs and RXRs.…”
Section: Discussionmentioning
confidence: 99%